BTT402- Fermentation Technology (Teknologi Fermentasi) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session February 2024 BTT402- Fermentation Technology (Teknologi Fermentasi) Duration : 2 hours (Masa : 2 jam)